TOPRSS: a simple clinical score to predict outcome and mortality in paediatric emergency department - S., Trishya Reddy; Raja, D. Venkatapathy (International Journal of Contemporary Pediatrics, 2021)
Background: To validate the clinical scoring system TOPRSS for the severity of the illness to prioritize care and predict outcomes in the emergency department. Methods: This prospective hospital-based observational study in 100 children for three months carried out. Cases<1-month age or>14 years excluded. Demographics data, provisional diagnosis, hemodynamics, seizures, and other clinical parameters were recorded on predesigned proforma at the time of admission. Final outcome of the patient, either discharge or death, was considered as the primary variable. Results: Out of 100 children, 92 were discharged and 8 deaths were recorded. Of the six variables, oxygen saturation and sensorium were found to be significantly associated with mortality. Logistic regression found that variables such as oxygen saturation and sensorium were strongly associated with mortality with a highly significant p value of 1% and variables such as pulse rate and seizures were also associated with mortality with a significant P value of 5%. Conclusions: For triage in pediatric emergency, a patient with two or more abnormal variables should be evaluated to facilitate admission as they have a potential risk of death. TOPRSS score being a simple clinical scoring system which does not require any expertise can applied at all levels of health care to identify critically ill patient referral to higher centre especially in regions of resource poor environment.